Use of Agent-Based Models in Investigation of Behavioral Finance Phenomena - Motloch, Pavel; Havlíček, David, 1985-; Matejašák, Milan; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2012)
This Bachelor thesis joins two areas which currently attracted increased attention --- Behavioral Finance theory and agent based models. Goal of this work was to overcome deficiencies of known agent based models and to create a model focusing on decision-making of individual agents, optimally using findings of Behavioral finance. We managed to find such a model and proved that it is capable of reproducing basic statistical properties of market prices, which is a basic test of the quality of the model. Its further use in investigation of Behavioral phenomena is currently impossible, because we are not able to sufficiently constraint the space of parameters. At the end of the thesis we discuss how it would be possible to overcome this obstacle.
Vedoucí práce: David Havlíček
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: finance [obor bakal. práce]; bakalářské práce; bachelor's theses